2019
DOI: 10.7186/bgsm68201910
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geophysical image of the hot spring in Rokan Hulu, Riau, Indonesia

Abstract: The first study of the hydrothermal system through the geophysical image in the area of Rokan Hulu hot spring is presented in this paper. The research employed integrated geophysical survey methods which consist of a geomagnetic, geoelectrical resistivity, and very low frequency (VLF) survey. Direct surface resistivity measurement was proposed and used to obtain a correlation of geological conditions with subsurface resistivity values and to correlate with VLF data. The geoelectrical resistivity survey used We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Another study also reported on the use of geoelectrical resistivity to detect the presence of leachate in landfill areas [10]. Geoelectrical resistivity has also been successfully used to image the presence of geothermal sources [11], detecting the slope of the sliding zone of the landslide zone [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported on the use of geoelectrical resistivity to detect the presence of leachate in landfill areas [10]. Geoelectrical resistivity has also been successfully used to image the presence of geothermal sources [11], detecting the slope of the sliding zone of the landslide zone [12].…”
Section: Introductionmentioning
confidence: 99%